The Influence of Pit and Fissure Sealants on Infrared Fluorescence Measurements - Diniz, M. B. [UNESP]; Rodrigues, J. A. [UNESP]; Hug, I.; Cordeiro, Rita de Cássia Loiola [UNESP]; Lussi, A. (Karger, 2008)
The aim of this in vitro study was to evaluate the influence of pit and fissure sealants on fluorescence readings using lasers. We selected 166 permanent molars and randomly divided them into 4 groups which were each treated with a different sealant (a commercially available clear sealant, 2 opaque sealants and an experimental nanofilled clear sealant). The teeth were independently measured twice by 2 experienced dentists using conventional laser fluorescence (LF) and a laser fluorescence pen device (LFpen), before and after sealing, and again after thermocycling to simulate the thermal stressing between the tooth and the dental materials. Friedman test showed no statistically significant changes using LF and LFpen for the commercial clear sealant group, although values tended to increase after sealing. However, the values increased significantly after thermocycling. There was a statistically significant decrease in fluorescence after application of opaque sealants. After application of the experimental nanofilled clear sealant, LF values increased only after thermocycling, whereas the LFpen values increased after sealing and after thermocycling as well. The intraclass correlation coefficient ranged from 0.87 to 0.96 for interexaminer and 0.82 to 0.94 for intraexaminer reproducibility. It was shown that pit and fissure sealants influence LF and LFpen readings, with the values increasing or decreasing according to the material used. In conclusion, both laser fluorescence devices could be useful as an adjunct to detect occlusal caries under unfilled clear sealants. Nevertheless, surfaces sealed with clear nanofilled material could be assessed using only the LF device. Copyright (C) 2008 S. Karger AG, Basel.
Keywords: Dental caries, diagnosis; Laser fluorescence; Pit and fissure sealants